Hexacene generated on passivated silicon - Eisenhut, Frank; Krueger, Justus; Skidin, Dmitry; Nikipar, Seddigheh; Alonso, Jose M.; Guitian, Enrique; Perez, Dolores; Ryndyk, Dmitry A.; Pena, Diego; Moresco, Francesca; Cuniberti, Gianaurelio (Giovanni) (Nanoscale, 2018)
On-surface synthesis represents a successful strategy to obtain designed molecular structures on an ultra-clean metal substrate. While metal surfaces are known to favor adsorption, diffusion, and chemical bonding between molecular groups, on-surface synthesis on non-metallic substrates would allow the electrical decoupling of the resulting molecule from the surface, favoring application to electronics and spintronics. Here, we demonstrate the on-surface generation of hexacene by surface-assisted reduction on a H-passivated Si(001) surface. The reaction, observed by scanning tunneling microscopy and spectroscopy, is probably driven by the formation of Si-O complexes at dangling bond defects. Supported by density functional theory calculations, we investigate the interaction of hexacene with the passivated silicon surface, and with single silicon dangling bonds.
CRIS-Team Scopus Importer:2022-04-14